The Influence of Apparatus Competence and Information Systems on Service Quality Impacts on Public Satisfaction at the Tourism, Youth and Sports Office of West Tanjung Jabung Regency - Niah, Niah; Bukit, Pantun; Rozi Yamali, Fakhrul (Journal of Accounting and Finance Management, 2026)
This study aims to describe and analyze the picture of competence, information systems, service quality, and public satisfaction at the Department of Tourism, Youth, and Sports of West Tanjung Jabung Regency, as well as to analyze the influence of apparatus competence and information systems through service quality on public satisfaction. This study was conducted at the Department of Tourism, Youth, and Sports of West Tanjung Jabung Regency. With a population of 1,121 people in 2025, while the sample size in this study uses Slovin's theory with a margin of error of 10% so that 92 people are obtained. This study uses a quantitative approach with a survey method and uses Partial Least Square (PLS) data analysis. The results of the study indicate that competence and information systems have an influence on public satisfaction, both directly and indirectly through service quality at the Department of Tourism, Youth, and Sports of West Tanjung Jabung Regency. This finding indicates that the positive influence of competence and information systems on public satisfaction does not occur directly, but is carried out (mediated) through improving service quality.